2014
DOI: 10.1080/19443927.2013.877964
|View full text |Cite
|
Sign up to set email alerts
|

Developing talent among young dancers: findings from the UK Centres for Advanced Training

Abstract: Developing talent among young dancers: Findings from the UK Centres for Advanced Training.Theatre, dance and performance training, 5(1): [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] http://dx.doi.org/10. 1080/19443927.2013.877964 Access to the published version may require subscription. AbstractThe identification and development of talent is a key concern for many dance educators, yet little research has been conducted in the area. In order to understand better how to optimise dance tal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…This could in part be explained by the small sample size and the fact that participants who only completed the questionnaire at Time 1 tended to score very highly. Furthermore, this finding aligns with previous evidence that SWB (Eid & Diener, 2004) and related constructs such as self-esteem (Aujla et al, 2014b) show little variation over time. An explanation for this comes from the Theory of Subjective Wellbeing Homeostasis (Cummins, 2010) which posits that under normal circumstances, SWB is maintained within a limited range by internal (e.g.…”
Section: Irissupporting
confidence: 90%
See 1 more Smart Citation
“…This could in part be explained by the small sample size and the fact that participants who only completed the questionnaire at Time 1 tended to score very highly. Furthermore, this finding aligns with previous evidence that SWB (Eid & Diener, 2004) and related constructs such as self-esteem (Aujla et al, 2014b) show little variation over time. An explanation for this comes from the Theory of Subjective Wellbeing Homeostasis (Cummins, 2010) which posits that under normal circumstances, SWB is maintained within a limited range by internal (e.g.…”
Section: Irissupporting
confidence: 90%
“…Recent studies indicate that dancers without disabilities have relatively high levels of SWB according to related measures such as self-esteem (e.g. Aujla, Nordin-Bates, Redding & Jobbins, 2014b;Nordin-Bates et al, 2011). However, the lack of quantitative studies of young dancers with disabilities means that currently there is no baseline data available about SWB that could be compared with other populations and over a period of time.…”
Section: Introductionmentioning
confidence: 99%
“…Further research could endeavour to create valid measures of technical and artistic dance skills in order to extend this research and more accurately investigate physical or actual competence. Moreover, while there are potential problems when using self-report measures among young people, the internal reliabilities of the measures and the stability of the results over time (see Aujla et al, 2014;Redding et al, 2011) suggests that the data were robust. Finally, the Centres for Advanced Training are a relatively new scheme, with an interest in dance science research and application.…”
Section: Limitationsmentioning
confidence: 94%
“…This study was part of a larger longitudinal research project investigating talent development among young dancers (Aujla, Nordin-Bates, Redding, & Jobbins, 2014;. Participants were female students recruited from eight UK Centres for Advanced Training, nationwide government-funded talent development programmes in dance.…”
Section: Participantsmentioning
confidence: 99%
“…Dance talent is generally understood to be multi‐faceted, comprised of various skills and abilities including technical skills, physical fitness, psychological motivation and resilience, and artistic ability (Walker et al, ). The most comprehensive study of dance talent development to date indicated that many factors associated with talent (such as muscular strength and flexibility) improve over time, demonstrating how at least certain aspects of talent are trainable given good‐quality training and a supportive environment (Aujla et al, ; Redding et al, ). As such, it appears that research efforts should focus on the content and delivery of training, rather than talent indicators.…”
Section: Introductionmentioning
confidence: 99%